Detection of plant pathogens using real‐time PCR: how reliable are late Ct values?. (4th September 2016) - Grosdidier, M.; Aguayo, J.; Marçais, B.; Ioos, R.
Abstract : Effective detection of pathogens from complex substrates is a challenging task. Molecular approaches such as real‐time PCR can detect pathogens present even in low quantities. However, weak real‐time PCR signals, as represented by high cycle threshold ( C t ) values, may be questionable. Therefore, setting a reliable C t threshold to declare a positive reaction is important for specific detection. In this study, five methods were assessed for their performance in determining a C t cut‐off value. These methods were based on the widely used probability of detection (POD) or receiver‐operating characteristic (ROC) approaches. Two important forest pathogens, Hymenoscyphus fraxineus and Fusarium circinatum, were used to set up three experimental frameworks that combined two types of substrates (seed lots and spore traps) and different PCR machines. The ROC‐based method emerged as the most complete and flexible method under various experimental conditions. It was demonstrated that the ROC method leads to a cut‐off value below which late C t results can reliably be considered indicative of positive test results. This cut‐off value must be determined for each experimental approach used. The method based on the distribution of a previously determined set of C t values corresponding to false‐positives appeared to be better adapted to detecting false‐negative results, and thus useful for testing potentially invasive pathogens.